Extension program in Applied Behavior Analysis to assist students with Autism - Benitez, Priscila; Freitas, Maria Clara de; Coelho, Gisele Roberta; Menotti, Ana Rubia Saes; Gomes, Máyra Laís de Carvalho; Zaine, Izabela; Domeniconi, Camila; Higbee, Thomas (Perspectivas em Análise do Comportamento, 2022)
The article aimed to describe a school service proposal in ABA (Applied Behavior Analysis), offered as an extension action by a public university, discussing the potentials and difficulties of its implementation in the public sphere, in partnership with the public school. The text was organized into three topics that discuss: partnership between university and school, as an extension action to provide educational services for people with autism; organization of the teaching curriculum to be worked on; service logistics through an interdisciplinary team of professionals and implementation indicators, with the number of people served, students involved in the team and considerations about the service as a Specialized Educational Service proposal. Challenges such as guaranteeing space, an interdisciplinary team and budgetary resources for maintaining the ABA service can be overcome, through the proposition of public education and health policies that guarantee interventions based on evidence.